History of Islam : Uthman ibn Affan - Aziz, Maulvi Abdul (Riyadh : Darussalam, 2012)
Darussalam, presents the entire History of Islam to our youth in language that appeals to them, in a simple yet lucid manner. The first four volumes in this series explore Islamic history during the period of the first Four Rightly-Guided Caliphs. Later volumes are devoted to the History of Islam. This book covers the third Caliph, Abu Uthman ibn Affan (R)
Includes index
Keywords: Islam; History